THE IMPLEMENTATION OF STORYBOARD IN TEACHING READING AT SEVENTH GRADE JUNIOR HIGH SCHOOL - Sofita; Muhammad Kurdi Wijaya (Universitas PGRI Palembang, 2025)
This research examines the use of interactive media based on storyboards in teaching descriptive texts to seventh-grade students at SMP Negeri 3 Burneh. The main aim is to evaluate how reading and speaking skills can be integrated through storyboard activities and to assess students’ engagement and comprehension. A qualitative descriptive approach was utilized, involving observations, interviews, and documentation. The results showed that storyboard media significantly aid students in understanding descriptive texts, while also stimulating their creativity and boosting their motivation. Students showed positive attitudes, with greater participation and enjoyment observed during lessons. These findings highlight the potential of visual-based media as an effective alternative strategy in English language instruction.